Comparison of salivary gland MRI and ultrasonography findings among patients with Sjögren's syndrome over a wide age range. (16th August 2021) - Takagi, Yukinori; Sasaki, Miho; Eida, Sato; Katayama, Ikuo; Hashimoto, Kunio; Nakamura, Hideki; Shimizu, Toshimasa; Morimoto, Shimpei; Kawakami, Atsushi; Sumi, Misa
Abstract: Objectives: This retrospective study compared MRI and US findings among patients with SS over a wide age range. Methods: Ninety patients with SS aged 8–84 years who had undergone both MRI and US examinations were divided into four groups according to age, as follows: <18 years (juvenile SS, JSS), 9 patients; 18–39 years, 12 patients; 40–69 years, 53 patients; >69 years, 16 patients. Imaging findings of parotid glands (PGs) and submandibular glands (SMGs) were compared among the four groups. Furthermore, the relationships within and between imaging findings and various clinical findings were examined. Results: On MRI, patients with JSS commonly exhibited multiple high-intensity spots in the PGs on MR sialography and fat-suppressed T2-weighted imaging. With increasing SS group age, the frequencies and numbers of the high-intensity spots were lower. Fat areas on MRI and hyperechoic bands on US were rarely observed in the PGs and SMGs of patients with JSS, whereas they were more common in patients with adult SS. In addition, the presence of hyperechoic bands on US, the presence of fat areas on MRI, and decreased salivary flow were associated with one another. Conclusion: Salivary gland imaging findings in patients with JSS were characterized by punctate sialectasis, whereas those findings in patients with adult SS were characterized by fatty degeneration. Distinct findings in patients with JSS and adult SS are likely to reflect differences in glandular lesion stage. MRI and US are presumably useful for evaluation of glandular lesion severity during follow-up.